2017
DOI: 10.1007/s12574-017-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of mitral annular disjunction detected by echocardiography and comparison with previously reported pathological data

Abstract: Mitral annular disjunction was detected not only in patients with a myxomatous mitral valve but also in normal cases. The number of MVPs was significantly larger in patients with mitral annular disjunction than patients without mitral annular disjunction. Further investigation is needed to clarify the clinical significance of the mitral annular disjunction detected by routine echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 13 publications
3
45
1
3
Order By: Relevance
“…Essayah et al reported that myxomatous mitral valve disease was a strongly associated with MAD (HR 5.04 95% CI 1.66–15.31), and other significant variables included mitral regurgitation severity (HR 3.12 95% CI 1.002–9.806) and mitral annulus diameter end‐systolic 2‐chamber length (HR 1.17 95% CI 1.05–1.30) . Konda et al reported that mitral valve prolapse was associated with MAD (OR 3.65 95% CI 1.70–7.83) . In the study by Torras 2018, all patients with MAD had bi‐leaflet prolapse and all patients with myxomatous mitral valve prolapse and sudden death had larger MAD distance (10.3 ± 1.5 vs 6.9 ± 1.7 mm) .…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Essayah et al reported that myxomatous mitral valve disease was a strongly associated with MAD (HR 5.04 95% CI 1.66–15.31), and other significant variables included mitral regurgitation severity (HR 3.12 95% CI 1.002–9.806) and mitral annulus diameter end‐systolic 2‐chamber length (HR 1.17 95% CI 1.05–1.30) . Konda et al reported that mitral valve prolapse was associated with MAD (OR 3.65 95% CI 1.70–7.83) . In the study by Torras 2018, all patients with MAD had bi‐leaflet prolapse and all patients with myxomatous mitral valve prolapse and sudden death had larger MAD distance (10.3 ± 1.5 vs 6.9 ± 1.7 mm) .…”
Section: Resultsmentioning
confidence: 61%
“…11 Konda et al reported that mitral valve prolapse was associated with MAD (OR 3.65 95% CI 1.70-7.83). 7 In the study by Torras 2018, all patients with MAD had bi-leaflet prolapse and all patients with myxomatous mitral valve prolapse and sudden death had larger MAD distance (10.3 ± 1.5 vs 6.9 ± 1.7 mm). 18 The observation about sudden cardiac death with longer MAD was also reported by Parazzollo Marra et al 5…”
Section: Re Sultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Передняя часть фиброзного кольца остается практически неподвижной, в то время как изменение размера атриовентрикулярного отверстия происходит за счет подвижности задней части. Митральное кольцо участвует в сокращении сердца, смещаясь вертикально к предсердию и уменьшаясь в размере во время систолы, к верхушке желудочка -во время диастолы [10,11].…”
Section: нормальная анатомия мкunclassified